Some features of providing of skilled legal help of advocate-defender (Journal of actual problems of jurisprudence, 2019)
This article examines the participation of defense counsel in criminal sudorpoizvodstve Republic of Kazakhstan. The author revealsthe fundamental rights of counsel at all stages of criminal proceedings.